Avian Influenza; Virus Characteristics, Clinical Symptoms and Antiviral Drugs - Coşkun Aslan (Turkish Journal of Agriculture: Food Science and Technology)
The viruses that cause avian flu (influenza) are highly contagious and highly variable viruses commonly found in birds. Wild birds in aquatic habitats are thought to be natural reservoirs for influenza viruses, but domestic poultry and other birds can also be infected. Influenza viruses belong to the orthomyxovirus family. Influenza A viruses are the only orthomyxoviruses known to naturally affect birds. Many bird species are susceptible to infection with influenza A viruses. Influenza A viruses have nucleocapsid and matrix proteins associated with their antigenic properties but are subtyped according to the hemagglutinin (H) and neuraminidase (N) antigens. In addition, avian influenza virus infections are considered to be one of the most important public health problems of the 21st century. Only in the last century, avian influenza viruses have created 4 different pandemics and have caused the death of a large number of poultry all over the world. The main purpose of this study is to provide information about avian influenza virus characteristics, important virus subtypes, clinical symptoms and antiviral drugs by analyzing the “Avian influenza” known as a poultry epidemic that has had significant effects in the 21st century.